Critical Appraisal of the Impact of Individual Surgeon Experience on the Outcomes of Minimally Invasive Distal Pancreatectomies: Collective Experience of Multiple Surgeons at a Single Institution. Issue 4 (August 2020) - Goh, Brian K.P.; Kabir, Tousif; Koh, Ye-Xin; Teo, Jin-Yao; Lee, Ser-Yee; Kam, Juinn-Huar; Cheow, Peng-Chung; Jeyaraj, Prema R.; Chow, Pierce K.H.; Ooi, London L.P.J.; Chung, Alexander Y.F.; Chan, Chung-Yip
Abstract : Background: Presently, there are limited studies analyzing the learning experience of minimally invasive distal pancreatectomies (MIDPs) and these frequently focused on a single surgeon or institution learning curve. This study aims to critically analyze the impact of individual surgeon experience on the outcomes of MIDP based on the collective experiences of multiple surgeons at a single institution. Methods: A retrospective review of 90 consecutive MIDP from 2006 to 2018 was performed. These cases were performed by 13 surgeons over various time periods. The cohort was stratified into 4 groups according to individual surgeon experience. The case experience of these surgeons was as follows: <5 cases (n=8), 6 to 10 cases (n=2), 11 to 15 cases (n=2), and 30 cases (n=1). Results: The distribution of the 90 cases were as follows: experience <5 cases (n=44), 6 to 10 cases (n=20), 11 to 15 cases (n=11), and 15 cases (n=15). As individual surgeons gained increasing experience, this was significantly associated with increasingly difficult resections performed, increased frequency of the use of robotic assistance and decreasing open conversion rates (20.5% vs. 100% vs. 9.1% vs. 0%, P =0.038). There was no significant difference in other perioperative outcomes. These findings suggest that the outcomes of MIDP in terms of open conversion rate could be optimized after 15 cases. Subset analyses suggested that the learning curve for MIDP of low difficulty was only 5 cases. Conclusion: MIDP can be safely adopted today and the individual surgeon learning curve for MIDP of all difficulties in terms of open conversion rate can be overcome after 15 cases.